Deletion mutants of the Escherichia coli K-12 mannitol permease: dissection of transport-phosphorylation, phospho-exchange, and mannitol-binding activities. - Grisafi, P L (1989)
We have constructed a series of deletion mutations of the cloned Escherichia coli K-12 mtlA gene, which encodes the mannitol-specific enzyme II of the phosphoenolpyruvate (PEP)-dependent carbohydrate phosphotransferase system. This membrane-bound permease consists of 637 amino acid residues and is responsible for the concomitant transport and phosphorylation of D-mannitol in E. coli. Deletions into the 3' end of mtlA were constructed by exonuclease III digestion. Restriction mapping of the resultant plasmids identified several classes of deletions that lacked approximately 5% to more than 75% of the gene. Immunoblotting experiments revealed that many of these plasmids expressed proteins within the size range predicted by the restriction analyses, and all of these proteins were membrane localized, which demonstrated that none of the C-terminal half of the permease is required for membrane insertion. Functional analyses of the deletion proteins, expressed in an E. coli strain deleted for the chromosomal copy of mtlA, showed that all but one of the strains containing confirmed deletions were inactive in transport and PEP-dependent phosphorylation of mannitol, but deletions removing up to at least 117 amino acid residues from the C terminus of the permease were still active in catalyzing phospho exchange between mannitol 1-phosphate and mannitol. A deletion protein that lacked 240 residues from the C terminus of the permease was inactive in phospho exchange but still bound mannitol with high affinity. These experiments localize sites important for transport and PEP-dependent phosphorylation to the extreme C terminus of the mannitol permease, sites important for phospho exchange to between residues 377 and 519, and sites necessary for mannitol binding to the N-terminal 60% of the molecule. The results are discussed with respect to the fact that the mannitol permease consists of structurally independent N- and C-terminal domains.